Carnitine and Infant Formulas - Firmansyah, Agus (Paediatrica Indonesiana, 1990)
Carnitine (gamma-trimethylamino-beta hydroxybutyric acid) is a quaternary amine which is capable of forming esters with a variety of acyl groups and was first identified by Gulawitsch and Krimberg in 1905. Carnitine deficiency was first noted by Fraenkel (1984) who observed that if certain insects were fed a diet free of carnitine, they would die in four to five weeks. Since that time, intensive studies had been done and led to suggestion that a primary function of carnitine was as a carrier molecule translocating long-chain fatty acids across the inner mitochondrial membrane to the matrix, where they underwent beta-oxidation (Friedman and Fraenkel, 1955). Carnitine is plentiful in human milk and milk-based infant formulas; however, it is lacking in supplemented soy formulas. Since newborn infant may not fully capable of synthesizing carnitine, they must receive an adequate intake of carnitine through the diet. This article describes some aspects of carnitine with special reference to the role of carnitine on fat metabolism.